SCIENTIFIC ACTIVITIES OF TIMURID PERIOD (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the scientific activities of Sayyid Sharif Jurjani(1340–1413) during his residence in Samarkand under the patronage of Amir Timur andanalyzes his contribution to the intellectual development of the Timurid era. The studyhighlights Amir Timur’s policy of gathering distinguished scholars from different regionsof the Islamic world and transforming Samarkand into a major center of learning. Specialattention is given to Jurjani’s arrival in Samarkand, his scholarly relationship with AmirTimur, and his famous intellectual debates with Sa'duddin Taftazani, which significantlyinfluenced the development of Islamic theology, logic, and philosophy. The article alsoexplores Jurjani’s role as a leading teacher in Timurid madrasas and examines theinfluence he exerted on a generation of prominent scholars, including Qadizada Rumi,Fathullah Shirvani, Ibn Arabshah, and others. Furthermore, the research discusses thedissemination of Jurjani’s works throughout the Islamic world and their enduring placein the educational curriculum of madrasas. The findings demonstrate that Jurjani’s nearlytwo decades of scholarly activity in Samarkand played a crucial role in strengtheningthe city’s status as a center of theoretical sciences and contributed significantly to theintellectual legacy of the Timurid Renaissance.
Keywords: Sayyid Sharif Jurjani, Amir Timur, Samarkand, Timurid Renaissance, Islamic sciences, madrasa education, Sa'duddin Taftazani, intellectual debates, theology, logic.